2017
DOI: 10.1002/lary.26796
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life outcomes of transoral robotic surgery with or without adjuvant therapy for oropharyngeal cancer

Abstract: 4. Laryngoscope, 128:403-411, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 22 publications
3
83
0
Order By: Relevance
“…There is a growing body of literature supporting the use of TORS as a minimally invasive treatment option with greater preservation of swallowing function and long‐term QOL compared to primary RT/CRT . When considering these QOL assumptions, TORS has also been described as a more cost‐effective treatment option in recent formal cost‐effectiveness analyses .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing body of literature supporting the use of TORS as a minimally invasive treatment option with greater preservation of swallowing function and long‐term QOL compared to primary RT/CRT . When considering these QOL assumptions, TORS has also been described as a more cost‐effective treatment option in recent formal cost‐effectiveness analyses .…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, by directly comparing QOL outcomes in patients receiving TORS alone vs TORS with adjuvant RT or CRT, Sethia et al found that the TORS alone group reported higher overall QOL across eating, social, and speech domains through 6 months after treatment . However, at 12 months, there were no longer significant differences in these outcomes in their prospective cohort of 111 patients . However, patients typically receive lower doses when treated with adjuvant therapy compared to primary RT/CRT, potentially resulting in decreased toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSS domains of poorer speech understandability and ability to eat in public have also been observed in patients with adjuvant treatment, with the poorest functioning occurring in those with adjuvant chemoradiotherapy . Others found poorer QOL in patients undergoing adjuvant treatment as compared to TORS surgery alone, with the poorest QOL found with adjuvant chemoradiotherapy …”
Section: Discussionmentioning
confidence: 99%
“…Further, although time to oral diet, diet type, and need for percutaneous endoscopic gastrostomy (PEG) placement have been examined in patients undergoing TORS, no studies have measured swallow functioning in terms of safety and efficiency after TORS procedures. Finally, many of these studies include evaluation of patients after adjuvant therapy and do not assess the functional impact of TORS alone on swallowing …”
Section: Introductionmentioning
confidence: 99%